PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN PARTISIPATIF DI KECAMATAN IBU SELATAN - KENO, DEVANTY CIMBERLY; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO (Sam Ratulangi University, 2017)
Summary: Planning is the first and most vital stage of development. Development planning is the main determinant ofsuccessful development that will be done within a country. Good planning and maturation will give birth to good results aswell. Therefore, in development planning must involve all parties in it not as objects but as subjects in the implementationof development. In planning the development of the very need of public participation.Participation is a bridge between government policy and the interests of the community, so that regional planning shouldbe done with a bottom-up model or so-called participatory planning. Participatory planning is planning that aims to involvethe interests of the people, and in the process involves the people (both direct and indirect) but in reality the planning itselfis still mostly done from the top (top down planning). This study aims to determine how the level of community participationin development planning. This research was conducted in Kecamatan Ibu Selatan Halmahera Barat District. The researchuses descriptive method with qualitative approach. Based on the results of interviews that have been done shows thatcommunity participation in development planning is still in the form of ideas and thoughts of ideas and suggestions. Needto do a deeper socialization to the community, so that the community is more active in the development planning that willbe done in the future.Keywords. Society participation